Impact of Sustained Use of a Multifaceted Computerized Quality Improvement Intervention for Cardiovascular Disease Management in Australian Primary Health Care. Issue 10 (24th October 2017) - Patel, Bindu; Peiris, David; Usherwood, Tim; Li, Qiang; Harris, Mark; Panaretto, Kathryn; Zwar, Nicholas; Patel, Anushka
Abstract : Background: We evaluated a multifaceted, computerized quality improvement intervention for management of cardiovascular disease (CVD) risk in Australian primary health care. After completion of a cluster randomized controlled trial, the intervention was made available to both trial arms. Our objective was to assess intervention outcomes in the post‐trial period and any heterogeneity based on original intervention allocation. Methods and Results: Data from 41 health services were analyzed. Outcomes were (1) proportion of eligible population with guideline‐recommended CVD risk factor measurements; and (2) the proportion at high CVD risk with current prescriptions for guideline‐recommended medications. Patient‐level analyses were conducted using generalized estimating equations to account for clustering and time effects and tests for heterogeneity were conducted to assess impact of original treatment allocation. Median follow‐up for 22 809 patients (mean age, 64.2 years; 42.5% men, 26.5% high CVD risk) was 17.9 months post‐trial and 35 months since trial inception. At the end of the post‐trial period there was no change in CVD risk factor screening overall when compared with the end of the trial period (64.7% versus 63.5%, P =0.17). For patients at high CVD risk, there were significant improvements in recommended prescriptions at end of the post‐trial period when compared with the end of the trial period (65.2% versus 56.0%, P <0.001). There was no heterogeneity of treatment effects on the outcomes based on original randomization allocation. Conclusions: CVD risk screening improvements were not observed in the post‐trial period. Conversely, improvements in prescribing continued, suggesting that changes in provider and patient actions may take time when initiating medications. Clinical Trial Registration: URL:http://www.anzctr.org.au . Unique identifier: 12611000478910.